On some conditions for the second moduli of continuity - Chaikovs’kyi, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.5We investigate the second moduli of continuity for functions from the space of continuous and periodic real functions and the space of functions uniformly continuous on the entire axis. For both  spaces, we give the negative answer to a question about necessity of one condition formulated by V. E. Geit, which is sufficient for a function to be a second module of continuity.